Literature in the Victorian Era and the Emergence of Modern Society (British Journal of Multidisciplinary and Advanced Studies, 2024)
It goes without saying that a time period of literature is inextricably linked to the culture of the time. An account of English literature from Compton-point Rickett's of view. If you want to view it properly and have a good sense of its worth, you need to limn it against a backdrop of its community events. The Victorian era is an excellent example of this fact. Majority of the authors of the time period display a critical consciousness in their work. In the Nineteenth century, literature was very near social reality, as noted by Compton-Rickett. Kingsley pens ardent social tracts disguised as stories; low food fuels Ebenezer Eliot's creativity; Elizabeth Barrett gives voice to The Cry of the Children; and Thomas Hood forever memorializes the tired seamstress and the despondent wretched. After detouring through German literature and European history, Carlye dives headfirst into contemporary political matters. No writer of literature has confronted industrialized issues with more understanding and more dazzling weirdness than Ruskin, who began his career as a commentator of the painting arts and now turns his attention to the more complicated art of living in the new century.